2012
DOI: 10.2460/javma.241.8.1075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orally administered electrolyte solution formulation on abomasal luminal pH and emptying rate in dairy calves

Abstract: Ingestion of a bicarbonate-containing OAE resulted in sustained abomasal alkalinization in dairy calves. Because persistently high abomasal luminal pH may facilitate growth of enteropathogenic bacteria, administration of OAEs containing a high bicarbonate concentration (> 70mM) is not recommended for calves with diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Moreover, prolonged abomasal passage and feeding of milk/MR‐based ORS may interfere with gastric acidification of ingesta and inactivation of ingested bacteria by which diarrhea may worsen due to entry of pathogenic bacteria into the small intestine (Smith et al . ). However, no adverse effects could be detected when treating diarrheic calves with HCO 3 – ‐containing ORS prepared in milk (Wenge et al .…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, prolonged abomasal passage and feeding of milk/MR‐based ORS may interfere with gastric acidification of ingesta and inactivation of ingested bacteria by which diarrhea may worsen due to entry of pathogenic bacteria into the small intestine (Smith et al . ). However, no adverse effects could be detected when treating diarrheic calves with HCO 3 – ‐containing ORS prepared in milk (Wenge et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, replacing sodium bicarbonate in an OES may have some appeal as several disadvantages have been identified when using high concentrations of bicarbonate in electrolyte products. High concentrations of bicarbonate alkalinize the abomasum, which could lead to a higher number of coliform bacteria that reach the small intestine, thus increasing the severity, duration, and mortality risk associated with diarrhea in calves (Smith et al, 2012). There is also concern that bicarbonate may interfere with milk clotting in the abomasum as previous studies identified that OES with a bicarbonate concentration >40 mEq/L has negative effects on milk clotting (Miyazaki et al, 2019).…”
Section: Short Communicationmentioning
confidence: 99%
“…This is particularly important when the OES contains sodium bicarbonate as alkalizing agent. The interference seems to be smaller or absent when the OES contains sodium acetate in its composition (SEN et al, 2006;MARSHALL et al, 2008;SMITH et al, 2012).…”
Section: Enteral Hydrationmentioning
confidence: 99%
“…Use of sodium bicarbonate (NaHCO 3 ) as an alkalizing agent is common in OES and has the advantage of combining directly with H + ions, exerting direct buffering effect. However, solutions with high HCO 3 -concentration alkalize the abomasum and the proximal portion of the small intestine, interfering with milk clotting and digestion (SMITH et al, 2012). As result of the increase in the intestinal lumen pH, bacterial growth is favored and can worsen the diarrhea (SEN et al, 2006;MARSHALL et al, 2008).…”
Section: Composition Of the Oral Electrolyte Solutions (Oes)mentioning
confidence: 99%
See 1 more Smart Citation